A study of retrospective and concurrent foreign language learning experiences: A comparative interview study in Hungary - Csizér, Kata; Kálmán, Csaba (Studies in Second Language Learning and Teaching, 2019)
Despite the fact that the influence of learning experiences on foreign language learning motivation has been widely acknowledged and emphasised, there are hardly any studies concentrating on these learning experiences. Hence, the aim of this study is to map the language learning experiences of former and current language learners in order to provide a detailed account of the possible components of the foreign language learning experience. Data were collected with the help of a qualitative interview schedule involving 22 language learners in two subsamples. Ten participants are English language teachers as former foreign language learners, while 12 students, current learners of English, have also been recruited. The most important result of our study is that foreign language learning experience seems to be a complex construct including immediate and present aspects as well as self-related components and attributions. Language learning success, the teacher’s personality, contact experiences, as well as attitudes towards the L2 seem to stand out as important components for both groups of learners. Apart from discussing the differences and similarities between retrospective and concurrent experiences, we will provide pedagogical and research-related implications as well.